Double Ventricular Responses Leading to Reversible Cardiomyopathy as Late Complication after Slow-Pathway Ablation. (30th September 2015) - Celikyurt, Umut; Gawaz, Meinrad; Schreieck, Juergen; Seizer, Peter
Abstract : Double ventricular response is a rare arrhythmia that results from simultaneous antegrade conduction over the fast and slow pathways of AV node. Double ventricular responses may lead to arrhythmia-related cardiomyopathy. As far as we know, there is not any reported reversible cardiomyopathy development that resulted from double ventricular responses to one atrial impulse after slow pathway ablation. We report a unique case of double ventricular response cardiomyopathy that has been developed 5 years after slow pathway ablation.